Bitter gourd (Momordica charantia L.) seed oil as a naturally rich source of bioactive compounds for nutraceutical purposes. Issue 1 (December 2016) - Yoshime, Luciana; de Melo, Illana; Sattler, José; de Carvalho, Eliane; Mancini-Filho, Jorge
Abstract Background Characterization of food lipids has triggered the development of applications for the food and health industries. Thus, the lipid profiles of an increasing number of fruits and their seeds have been characterized and numerous bioactive components have been isolated. The bitter gourd seed oil has aroused great interest because it contains relevant amounts of conjugated fatty acid α-eleostearic acid (C18:3 9c 11t 13t ), a positional and geometric isomer of α-linolenic acid. The aim of this paper was to evaluate the phytochemical composition and quality parameters of the seed oil of bitter gourd grown in Brazil. Methods Bitter gourd was purchased from CEAGESP (Brazilian company of fresh food storages and warehouses). Seeds were lyophilized, and their oil was extracted using the Soxhlet and Folch extraction methods. The profiles of fatty acids and phytosterols were analyzed by gas chromatography, and the acidity and peroxide values were evaluated by methods of the American Oil Chemists' Society (AOCS). Results The Soxhlet extraction (40 %w /w ) resulted in a higher yield of bitter gourd seed oil than the Folch extraction (16 %w /w ). For both methods, α-eleostearic acid (56 and 58 %) was the major lipid in bitter gourd seed oil, followed by stearic acid (C18:0; 32 and 27 %). The oil displayed high content of phytosterols (886 mg/100 g), mainly β-sitosterol, and low acidity and peroxide values. Conclusions Bitter gourd seed oil from Brazil is an oil of good quality and its high contents of α-eleostearic acid and phytosterols with potential health-beneficial properties make it an attractive plant byproduct.